SENI LUKIS KARYA WIRYONO PERIODE 2006-2012 - Wicaksana, Arif; Cholis, Henry (Institut Seni Indoensia Surakarta, 2017)
This article discusses the paintings by Wiryono in the 2006-2012 period which are unique in terms of techniques, shapes, fantasies, metaphors, and aesthetics that are displayed in the works. The type of research used is qualitative research using a phenomenological approach that obtains data through direct observation in the field, interviews, literature reviews and other visual data. To dissect the work, Monroe C. Beardsley's theory of creativity was used.Â Keywords: aesthetics, wiryono, painting.